2000
DOI: 10.1017/s0007114500000179
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the extent of degradation of ruminant feeds from a description of their gas production profiles observedin vitro: comparison of models

Abstract: An evaluation of general models that describe gas production profiles is presented. The models are derived from first principles by considering a simple three-pool scheme and permit the extent of ruminal degradation to be calculated, as described in the companion paper. The models evaluated were the generalized Mitscherlich, simple Mitscherlich, generalized MichaelisMenten, simple Michaelis-Menten, Gompertz, and logistic. Five sets of gas production data consisting of 216 curves, obtained using a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
3
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 29 publications
(69 reference statements)
1
36
3
3
Order By: Relevance
“…Adicionalmente, Fondevila & Barrios (2001) mencionaram que os modelos multicompartimentais são mais adequados quando se utilizam um número muito grande de leituras, tal como ocorre nos sistemas automatizados, e que isso não ocorre quando o número de leituras é limitado, porém, de acordo com Pell et al (2000) n>16, leituras mais freqüentes na fase inicial são suficientes para proporcionar um ajuste adequado. No entanto, alguns autores (Dhanoa et al, 2000;France et al, 2000) recomendaram a utilização de modelos unicompartimentais devido a interpretação mecanicista, em preferência a puramente empírica dos modelos multicompartimentais.…”
Section: Resultsunclassified
“…Adicionalmente, Fondevila & Barrios (2001) mencionaram que os modelos multicompartimentais são mais adequados quando se utilizam um número muito grande de leituras, tal como ocorre nos sistemas automatizados, e que isso não ocorre quando o número de leituras é limitado, porém, de acordo com Pell et al (2000) n>16, leituras mais freqüentes na fase inicial são suficientes para proporcionar um ajuste adequado. No entanto, alguns autores (Dhanoa et al, 2000;France et al, 2000) recomendaram a utilização de modelos unicompartimentais devido a interpretação mecanicista, em preferência a puramente empírica dos modelos multicompartimentais.…”
Section: Resultsunclassified
“…In fitting the present models the lag phase can simply be deleted from the equation if it does not significantly improve the fit of the curve, except in the case of the generalized Mitscherlich where a lag, albeit small, is needed to prevent a mathematical discontinuity in m at zero time. There seems little to choose between the present models biologically and mathematically, so choice of best model should be made on the basis of fitting criteria (see Dhanoa et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As observed in Figure 1, the highest gas volume in BF showed that F was more degradable in the rumen to provide more fermentable substrate, given the fact that the gas produced is directly proportional to the rate at which the substrate is degraded [17]. The minimum gas production in FPSB might be due to the prevention of substrate availability for bacteria by prill fat or the possible toxicity of microorganisms.…”
Section: Discussionmentioning
confidence: 87%